Teaching that changes lives : 12 mindset tools for igniting the love of learning - Adams, Marilee (2013)
"Building on the success of her classic, bestselling book, Change Your Questions, Change Your Life (over 100,000 copies sold), Marilee Adams shows in this new book how teachers and other education professionals can change their own and their students' lives by developing an active, inquiring mindset and igniting a lifelong love of learning"--
Keywords: Thought and thinking -- Study and teaching -- United States; Cognition in children; Effective teaching -- United States; Educational change -- United States; EDUCATION / Professional Development; EDUCATION / Leadership; EDUCATION / Philosophy & Social Aspects